Ecological niche separation of two sympatric insectivorous lizard species in the Namib Desert. (January 2016) - Murray, Ian W.; Fuller, Andrea; Lease, Hilary M.; Mitchell, Duncan; Hetem, Robyn S.
Abstract: Individual lizard species may reduce competition within a habitat by diverging along one or more niche dimensions, such as spatial, temporal or dietary dimensions. We compared the morphology, activity patterns, microhabitat characteristics, thermal biology and feeding ecology of two species of diurnally active sympatric insectivorous lizards in the Namib Desert, the Husab sand lizard, Pedioplanis husabensis, and Bradfield's Namib day gecko, Rhoptropus bradfieldi . Pedioplanis husabensis and R. bradfieldi had similar snout-vent lengths (49–52 mm), but P. husabensis (2.5–3.0 g) weighed less than R. bradfieldi (3.1–3.9 g). The actively foraging Pedioplanis husabensis specialized on a termite diet (71% of all prey, found in 91% of fecal pellets), while the sedentary sit-and-wait foraging R. bradfieldi specialized on ants (87% of all prey, found in 100% of fecal pellets). Pedioplanis husabensis also had a higher active body temperature and often was found on warmer substrates than was R. bradfieldi . Despite occurring in the same habitat, these two lizard species do not occupy the same ecological niche space. Highlights: Sympatric Pedioplanis husabensis and Rhoptropus bradfieldi forage on distinct and non-overlapping arthropod prey. Within a site, the lizards Pedioplanis husabensis and Rhoptropus bradfieldi occupy different microhabitats. Microhabitat substrate temperature is a significantly better predictor of Rhoptropus bradfieldi body temperature than it is for Pedioplanis husabensis body temperature. Pedioplanis husabensis and Rhoptropus bradfieldi occurring at the same site partition the available niche space.